(untitled) - FAO (Rome, Italy, 1998)
The book describes the components of survey and monitoring systems for the purpose of pest detection and the supply of information for use in pest risk analyses, the establishment of pest free areas and, where appropriate, the preparation of pest lists
Keywords: plants, protection of